1991
DOI: 10.1128/aac.35.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities in vitro and in vivo and pharmacokinetics of cefquinome (HR 111V), a new broad-spectrum cephalosporin

Abstract: Cefquinome is a new injectable aminothiazolyl cephalosporin derivative. It is stable against chromosomally and plasmid-encoded I8-lactamases and has a broad antibacterial spectrum. Staphylococcus aureus, streptococci, Pseudomonas aeruginosa, and members of the family Enterobacteriaceae (Escherichia coli, Salmonella spp., Klebsiella spp., Enterobacter spp., Citrobacter spp., and Serratia marcescens) are inhibited at low concentrations. Cefquinome is also active against many strains of methicillin-resistant stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
110
1
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 15 publications
(11 reference statements)
21
110
1
3
Order By: Relevance
“…We can conclude that cefquinome had no effect on the Bacteroides-Prevotella group, as was shown by Limbert et al (28), who found that 11 of the 14 tested strains were resistant to cefquinome at an in vitro concentration higher than 100 µg/mL (28).…”
Section: Time Course Evolution Of Gut Microbiota During Cefquinome Trsupporting
confidence: 52%
See 1 more Smart Citation
“…We can conclude that cefquinome had no effect on the Bacteroides-Prevotella group, as was shown by Limbert et al (28), who found that 11 of the 14 tested strains were resistant to cefquinome at an in vitro concentration higher than 100 µg/mL (28).…”
Section: Time Course Evolution Of Gut Microbiota During Cefquinome Trsupporting
confidence: 52%
“…The high in vivo activity of cefquinome against the genus Bifidobacterium was supported by the absence of detection during the treatment period (28). Bifidobacteria were detected before and after the treatment, while during cefquinome administration from Day 1 to Day 3, Bifidobacterium levels dropped below the LOD (5 log 10 CFU/g).…”
Section: Time Course Evolution Of Gut Microbiota During Cefquinome Trmentioning
confidence: 90%
“…Today, S. aureus is recognized as the most commonly implicated organism (22,23). Cefquinome possesses a broad antibacterial spectrum (against, e.g., S. aureus, including MRSA) and favorable pharmacokinetics; thus, it merits further investigation into its chemotherapeutic properties (7). The use of antimicrobial PK-PD analyses to identify the pharmacodynamic activity of antimicrobial agents through the integration of the PK properties, in vitro potency (MIC), and outcome is one approach that has proven helpful for the design of effective dosing regimens in humans and animals, as well as in the development of appropriate in vitro susceptibility breakpoints (15,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Cefquinome (formerly HR 111V) is a fourth-generation cephalosporin developed solely for veterinary use. It displays antimicrobial activities in vitro and in vivo against a broad spectrum of Gram-positive and Gram-negative bacterial species, including methicillin-resistant and methicillin-susceptible S. aureus, and it is considered to be highly stable against ␤-lactamases encoded by chromosomes and genes on plasmids (7)(8)(9).…”
mentioning
confidence: 99%
“…A significant enhancement of activity and an extension of the antibacterial spectrum were achieved by the introduction of a methoxyimino-aminothiazolyl moiety into the acyl side chain of the cephalosporin, which made it resistant to inactivation by b-lactamases [6][7][8][9][10][11]. The quaternary quinoline group at position 3 in the cefem ring and the resulting zwitterionic structure facilitate the rapid penetration of cefquinome across the biological membranes of animals and bacteria, ensuring its fast bactericidal action after injection.…”
Section: Introductionmentioning
confidence: 99%